Donor Human Milk: Effects of Storage and Heat Treatment on Oxidative Stress Markers - Bertino, Enrico; Peila, Chiara; Cresi, Francesco; Maggiora, Elena; Sottemano, Stefano; Gazzolo, Diego; Arslanoglu, Sertac; Coscia, Alessandra (Frontiers in Pediatrics, 2018)
Mother’s own milk is the first choice for the feeding and nutrition of preterm and term newborns. When mother’s own milk is unavailable or in short supply donor human milk (DM) could represent a solution. Heat treatment and cold storage are common practices in Human Milk Banks (HMBs). Currently, Holder pasteurization process is the recommended heat treatment in all international guidelines. This method is thought to lead to a good compromise between the microbiological safety and nutritional/biological quality of DM. Moreover, storage of refrigerated milk is a common practice in HMBs and in NICUs. Depending on the length and on the type of storage, human milk may lose some important nutritional and functional properties. The available data on oxidative stress markers confirm that pasteurization and refrigeration affected this important elements to variable degrees, even though it is rather difficult to quantify the level of deterioration. Nonetheless, clinical practice demonstrates that many beneficial properties of human milk are preserved, even after cold storage and heat treatment. Future studies should be focused on the evaluation of new pasteurization techniques, in order to achieve a better compromise between biological quality and safety of DM.